Double Infection in a Patient with Chronic GVHD Post Allogeneic Transplant: “Hickam's Dictum” Trumps “Occam's Razor”!—A Case Report with Review of Literature - Fen Saj; Vendoti Nitheesha Reddy; Smita Kayal; Biswajit Dubashi; Rakesh Singh; Noyal Mariya Joseph; Prasanth Ganesan (Indian Journal of Medical and Paediatric Oncology)
Double pneumonia with Pneumocystis jirovecii (PCP) and Mycobacterium tuberculosis (MTB) has been reported in patients with acquired immune deficiency syndrome. A similar immune-suppressed state exists in allogeneic transplant survivors treated for graft-versus-host disease (GVHD). The clinical features and imaging findings could be quite similar in both the etiologies. Reaching a timely diagnosis and initiation of appropriate therapy is essential to prevent complications. We report a patient who had concurrent PCP and MTB pneumonia while on treatment for chronic GVHD. We describe the diagnostic challenge, the treatment, and outcome of this patient. We intend to sensitize physicians to consider more than one etiology in this subset of patients.